Online Survey on the Source of Information, Knowledge, and Perceptions towards COVID-19 among Health Care Workers and Health Students in Nepal: A Comparative Study (Global Journal of Medical Research, 2020)
The burgeoning cases of COVID-19 are the major concern and challenges across the world. However, there are different drugs on the row for the clinical trial. Misinformation and misguidance from the unreliable source of information, misunderstanding, lack, or inadequate awareness among people, and poor sanitation procedure could lead to the rapid transmission of infection in the community. The basic objective was to study the knowledge and perception of HCWs and students about COVID-19.
Keywords: COVID-19; knowledge; online survey; perceptions; source of information; health care workers